STUDI EVALUATIF IMPLEMENTASI PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 - Marinu Waruwu (Jurnal Administrasi Pendidikan, 2023)
The purpose of this research is to identify the evaluation of online learning implementation due to Covid-19. The online learning done is a learning that uses information technology application. The research object is teachers in elementary school. Evaluation is done with survey method by asking teacher evaluations toward online learning implementation. The evaluation result shows that online learning has impacts on teacher skills and knowledge improvement, technology control, autonomic, creativity, self-sufficiency, improvement of student knowledge and skills, learning process and resources readiness such as teacher facility, readiness. Meanwhile, online learning does not significantly impact on mastery learning, effective interaction, improvement of characters, motivation and assessment accuracy. In conclusion, online learning impacts on academic improvement, but lesser impact on non-academic such as improvement of character building.